Eimeria bovis-mediated modulation of the host cell cholesterol metabolism - Hamid, Penny Humaidah; Justus Liebig University Giessen (My University, 2014)
During first merogony E. bovis forms large-sized macromeronts containing >120,000 merozoites. Given thatobligate intracellular replicating coccidians are generally considered as auxotrophic for cholesterol synthesis and that asingle sporozoite stage cannot provide all components necessary for this nutrient and energy demanding process, the parasite needs to scavenge molecules from the endothelial host cell. Especially for the massive offspring membrane production, large amounts of cholesterol are indispensable for a successful replication process. Here, the influence of E. bovis infections on host cell cholesterol metabolism was analyzed.Free cholesterol and neutral lipids were shown to be differentially distributed in sporozoite stages. Thus, free cholesterol mainly occurred in the apical complex and in the pellicles of sporozoite and merozoite I stages whilst neutral lipids accumulated in refractile bodies of the sporozoites. Both stages showed cytoplasmic lipid droplet (LD)-like structures indicating their capability for lipid storage. Kinetic analyses revealed enhanced levels of free cholesterol during E. bovis macromeront development. A massive increase of LD formation in immature macromeronts suggested these organelles and esterified cholesterol (which is stored in LDs) as important lipid source for E. bovis. In agreement, an artificial increase of cellular LDs led to improved merozoite I production and pharmacological blockage of cholesterol esterification abrogated E. bovis development. Transcriptional profiling of infected host cells in times of macromeront formation indicated that E. bovis modulates both pathways of cholesterol acquisition, i. e. LDL-promoted uptake of extracellular cholesterol sources and host cellular de novo synthesis. Thus, the gene transcription of several molecules being involved in cellular cholesterol de novo synthesis via the mevalonate biosynthesis pathway (e. g. HMG-CoA synthase, HMG-CoA-reductase and squalene epoxidase) and of transcripts of the LDL-receptor (LDLR) and the oxidised LDL receptor 1 (OLR1) were equally found up-regulated in infected host cells. Furthermore, cellular cholesterol processing appeared enhanced since key molecules, such as cholesterol-25-hydroxylase and acyl-CoA acetyltransferase, were significantly up-regulated in infected cells, the latter of which promotes cellular cholesteryl ester synthesis and lipid droplet biogenesis. The key role of cholesterol de novo synthesis and processing was furthermore confirmed via pharmacological blockage applying the following inhibitors: lovastatin, zaragozic acid, CI976 and C75 targeting HMG-CoA-reductase, squalene synthase, acyl-CoA cholesterol acyltransferase and fatty acid synthase, respectively. In summary, all inhibitors significantly interfered with E. bovis macromeront formation and merozoite I production in a dose-dependent manner. Dose effect responses identified lovastatin as the most effective compound, followed by CI976, C75 and squalestatin, respectively. Overall, merozoite I production was inhibited by 99.6, 99.7, 84.6 and 70.2 % via lovastatin, CI976, C75 and zaragozic acid treatments, respectively. Concerning macromeront development, both, the rate and size of meronts were affected by inhibitor treatments. Respective effects were characterized by developmental arrest and meront degradation. The pivotal role of LDL-promoted host cellular incorporation of exogenous cholesterol for parasite replication was underlined by enhanced binding of non-modified and acetylated LDL on E. bovis-infected cells. In addition, significantly increased levels of surface LDLR expression were detected on meront-carrying host cells. Furthermore, cholesterol and LDL enrichments of the cell culture medium boosted parasite replication. Besides LDLR, we additionally identified the scavenger receptor OLR1 (oxidized LDL receptor 1) as a key molecule of parasite-triggered LDL uptake since both, gene transcription and protein expression was found enhanced in infected cells.Overall, these results indicate that E. bovis massively modulates the host cell cholesterol metabolism to guarantee its intracellular growth and replication.

E. bovis bildet als strikt intrazellulärer Erreger im Rahmen der ersten Merogonie sog. Makromeronten aus, in denen mehr als 120.000 Merozoiten produziert werden. Dieser nährstoff- und energiefordernde Prozess kann nicht von Sporozoiten allein getragen werden. Dementsprechend muss der Parasit den Wirtszellmetabolismus modulieren, um seine erfolgreiche Replikation abzusichern. Dies betrifft aufgrund der massiv geforderten Membranbiogenese für die Merozoitenproduktion insbesondere den Cholesterolmetabolismus der infizierten Wirtszelle, der Gegenstand dieser Untersuchungen war. In freien Stadien von E. bovis (Sporozoiten, Merozoiten I) zeigte sich eine unterschiedliche Verteilung von freiem Cholesterol und neutralen Fetten bzw. Lipidtröpfchen (LT). Während freies Cholesterol bevorzugt im Apikalkomplex und in der Pellikula nachgewiesen wurde, waren Cholesterylester bzw. neutrale Fette ausschließlich in refraktilen Körperchen nachzuweisen. Zudem wurden LT-ähnliche Strukturen im Zytoplasma beider Stadien gefunden, was auf die Befähigung zur Lipidspeicherung seitens des Parasiten schließen lässt. Analysen zur E. bovis-Makromerontenreifung zeigten eine vermehrte Präsenz von von freiem Cholesterol in infizierten Zellen. Ein massiver Anstieg der LT-Bildung in immaturen Makromeronten wies auf eine entscheidende Rolle dieser Organelle bzw. ihrer Inhalte wie z. B. Cholesterylester als Lipidquelle hin. Die Relevanz von LT bzw. Cholesterylestern konnte über artifizielle Steigerung der LT in Wirtszellen über gesteigerte Merozoiten I-Produktion als auch über pharmakologische Blockade der Cholesterolveresterung mit ausbleibender Parasitenproliferation bestätigt werden.Analysen zur Gentranskription von Wirtszellen während der Makromerontenbildung wiesen auf eine gleichzeitige Modulation beider Wege der Cholesterolakquise, d. h. von wirtszellulärer de novo-Synthese als auch der LDL-vermittelte Aufnahme exogenen Cholesterols, hin. Entsprechend waren Gentranskripte diverser, in die zelluläre de novo-Synthese von Cholesterol eingebundener Moleküle (z. B. HMG-CoA-Synthase, HMG-CoA-Reduktase, Squalenepoxidase) als auch von LDL-Rezeptoren (LDL-Rezeptor, oxidised LDL-Rezeptor 1) gegen Ende der Merontenreifung hochreguliert. Zusätzlich wurde die Prozessierung zellulären Cholesterols über E. bovis-Infektionen verstärkt, da sowohl die Cholesterol-25-Hydroxylase als auch die Acyl-CoA-Acyltransferase hochreguliert wurden, wobei letztere die Synthese von Cholesterylestern sowie die Biosynthese der Lipidkörperchen vermittelt.Die entscheidende Rolle der wirtszellulären de novo-Synthese von Cholesterol wurde zusätzlich über Inhibitionsstudien belegt, bei der Inhibitoren zur Blockade der HMG-CoA-Reduktase (Lovastatin), Squalensynthase (Zaragozic Acid), Acyl-CoA:cholesterol acyltransferase (CI976) and Fettsäuresynthase (C75) verwendet wurden. Hier zeigte sich, dass alle verwendeten Inhibitoren einen blockierenden, dosis-abhängigen Einfluss auf die Makromerontenbildung und Merozoiten I-Produktion hatten. So wurde die Merozoiten I-Synthese zu 99,6, 99,7, 84,6 und 70,2 % überLovastatin, CI976, C75 and Zaragozic Acid gehemmt. Zusätzlich wurde die Größenentwicklung der Makromeronten als auch respektive Infektionsraten negativ beeinflusst und es zeigten sich Entwicklungsabbrüche als auch Degradierungseffekte bei Makromeronten.Die entscheidende Rolle der LDL-vermittelten Cholesterolaufnahme für die Parasitenproliferation wurde über signifikant gesteigerte Bindungsreaktionen von nicht-modifizierten und acetyliertem LDL an Meronten-tragenden Wirtszellen als auch über eine signifikant erhöhte Oberflächenexpression von LDL-Rezeptoren bei infizierten Zellen untermauert. Zudem führte eine Anreicherung des Zellkulturmediums mit LDL oder Cholesterol zu einer gesteigerten Merozoiten I-Produktion. Neben dem klassischen LDL Rezeptor konnten wir mit OLR1 einen zusätzlichen, sog. Scavenger -Rezeptor identifizieren, der sowohl auf Transkript- als auch Proteinebene in infizierten Zellen hochreguliert war und aller Wahrscheinlichkeit nach an die E. bovis-vermittelte Steigerung der wirtszellulären LDL-Aufnahme beteiligt ist.Zusammenfassend zeigen vorliegende Ergebnisse, dass E. bovis massivst in den Cholesterolhaushalt der Zelle eingreift, um sein intrazelluläres Wachstum und Entwicklung abzusichern.
Eimeria bovis-vermittelte Modulation des Cholesterolmetabolismus der Wirtszelle
Keywords: ddc:630